How grim is pancreatic cancer? - Elroy Patrick Weledji; George Enoworock; Martin Mokake; Motaze Sinju (Frontiers Media S.A., 2016)
Pancreatic ductal carcinoma continues to be the most lethal malignancy with rising incidence. It is the fourth most common cause of cancer death in the western world due to its low treatment success rate. In addition, because of its rapid growth and silent course, diagnosis is often only established in the advanced stages. As one of the most aggressive malignancies, the treatment of this disease is a great challenge to clinicians. This paper reviewed the natural history of pancreatic cancer, the current clinical practice and the future in pancreatic cancer management.